Prenatal Diagnosis of Bilateral Ectrodactyly and Radial Agenesis Associated with Trisomy 10 Mosaicism - Jonathan Lévy; Jean-Marie Jouannic; Julien Saada; Ferdinand Dhombres; Jean-Pierre Siffroi; Marie-France Portnoï (Case Reports in Genetics)
Ectrodactyly or split hand and foot malformations (SHFMs) are rare malformations of the limbs, characterized by median clefts of the hands and feet, syndactyly, and aplasia and/or hypoplasia of the phalanges. They represent a clinically and genetically heterogeneous disorder, with both sporadic and familial cases. Most of the genomic rearrangements identified to date in some forms of SHFM are autosomal dominant traits, involving various chromosome regions. Bilateral radial ray defects comprise also a large heterogenous group of disorders, including trisomy 18, Fanconi anemia, and thrombocytopenia-absent-radius syndrome, not commonly associated with ectrodactyly. The present paper describes a case of ectrodactyly associated with bilateral radial ray defects, diagnosed in the first trimester of pregnancy, in a fetus affected by trisomy 10. Only four cases of sporadic and isolated ectrodactyly, diagnosed by ultrasonography between 14 and 22 weeks’ gestation, have been reported. To our knowledge, the present case is the first report of mosaic trisomy 10 associated with SHFM and radial aplasia. Trisomy 10 is a rare lethal chromosomal abnormality, most frequently found in abortion products. Only six liveborn mosaic trisomy 10 infants, with severe malformations, dead in early infancy, have been reported. A severe clinical syndrome can be defined, comprising ear abnormalities, cleft lip/palate, malformations of eyes, heart, and kidneys, and deformity of hands and feet and most often associated with death neonatally or in early infancy.